Low doses of gamma irradiation potentially modifies immunosuppressive tumor microenvironment by retuning tumor-associated macrophages: lesson from insulinoma - Prakash, Hridayesh; Klug, Felix; Nadella, Vinod; Mazumdar, Varadendra; Schmitz-Winnenthal, Friedrich Hubertus; Umansky, Liudmila (Carcinogenesis, 2016)
Summary. Total body gamma irradiation in neoadjuvant settings potentially retunes immunosuppresive tumor microenvironment particularly by tuning tumor-associat
Gesehen am 10.03.2020